Understanding Health Insurance from the Perspective of an Ecosystem: A Systematic Review and Meta-Synthesis - Somayeh Noori Hekmat; Rohaneh Rahimisadegh; Mohammad Hossein Mehrolhasani; Mohammad Jafari Sirizi (Shahid Sadoughi University of Medical Sciences, 2022)
Background: The health insurance ecosystem involves all the organizations and institutions which act as ecosystem actors in accordance with the objectives, values and functions of the ecosystem as its elements. Comprehensive understanding of the elements and actors of this ecosystem can be effective in improving its current status and in the future. Thus, the present study aimed to discuss the key elements (objectives, values and functions), as well as the actors of the health insurance ecosystem by a systematic review method. Methods: This systematic review study was conducted in January 2021 using the six-step Walsh and Downe technique in the form of meta-synthesis. The question proposed a search strategy using the SPIDER framework, and the search was done in PubMed, Scopus, Web of Science ,Cochrane and Persian database of Magiran without considering a specific time and place. Content analysis method and MAXQDA 2020 were used to combine the findings. the Mixed Methods Appraisal Tool (MMAT) evaluation checklist version 2018 was used to evaluate quality of studies. Results: 1410 articles were found in major databases, and 10 papers were found by manual searching using the search strategy. In addition, 612 duplicate records were removed from the search results after entering the results in EndNote X7 software. Ultimately, 9 studies reached the stage of quality evaluation and meta-synthesis. The selected studies were reviewed one by one, and their key concepts and themes were identified using content analysis method. Finally, the list of actors and key elements of the health insurance ecosystem was made. Conclusion: Establishing fair participation and financial protection were identified as the most important key elements in the health insurance ecosystem, achieved through governance functions, resource supply, and service delivery in the context of an integrated and transparent structure. Applying governance is the most important role of ecosystem, forming the necessary participation and coordination between the actors in different roles, and regulating the interactions between them through mechanisms such as tariffs and the payment system. The role played by many actors with different roles or different roles by one actor in the ecosystem results in complexity and conflict of interest.